Expression pattern of the autophagy related proteins Beclin1 and LC3B in tuberculous wound tissues. (June 2021) - Zhou, Keqiang; Su, Yingjun; Jia, Chiyu
Tuberculous wound therapy is a major challenge in clinical practice, due to the protracted disease course, high recurrence rate, and an unclear pathogenesis. We explored the expression patterns of Beclin1 and LC3B in tuberculous wound tissues in human tuberculous chronic wound and normal tissues was assayed by immunohistochemistry. Rat models of tuberculous wounding were induced by the Bacillus Calmette-Guerin (BCG) method. Beclin1 and LC3B protein expression in human tuberculous wound tissues differed from that of normal skin and non-tuberculous chronic wound tissues.In rat tuberculous wound tissues, expression of Beclin1 and LC3B mRNA time-dependently changed post-infection. Abnormal fluctuation of autophagy protein in the development of tuberculosis wound could be one of the causes for the repeated occurrence and protracted disease course of the tuberculous wound.